[iLahleko - Loss] - Qhali, Itumeleng (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
My thesis is a collection of poems and prose that explores the disjunction of losses for women and children across the two languages I inhabit, isiXhosa and English. Ukulahlekelwa lithemba, ukudukelwa yingqondo, ukholo, ubuwena, umzimba nothando. For me, isiXhosa captures the innate musicality and deep emotions within a word or a sound that are not available in English. On the other hand, English readily produces visceral images that are more difficult for me to access in isiXhosa. Kolu phononongo ndikwasebenzisa namagama emboleko ukuze ndikhulise isigama. Ndisebenzisa amagama azibeka zinjalo iimvakalelo, angqalileyo kuncwadi lwesiXhosa. Ndisebenzisa zombini ilyric form kunye neprozi ngenxa yesingqi esiphuhliswa yilyric, nangenxa yenkululeko umbali ayifumanayo kwiprozi. As a bilingual writer ndifuthelwe sisingqi nobunzulu bentlungu obufumaneka in the translated and bilingual works of Isabella Motadinyane, noMarina Ivanovna Tsvetaeva, imibongo yeDaikwan eguqulwe nguStephen Watson ethi Song of the Broken String; iimbongi zespanish ezinjengo Antonia Machado; ngendlela abasebenzisa ngayo ulwimi lwabo ukunabisa nokugqithisa umyalezo ngeentlungu abadibana nazo, bakwanaso nesingqi somculo othuthuzelayo kwimibongo yabo. The structure of my thesis is inspired by the innovative mixed genre layout of Sindiswa Busuku-Mathese's Loud and Yellow Laughter, and the new formats of isiXhosa writing presented in Mthunzikazi Mbugwana's poetry. My work has also been shaped by the visceral imagery and briefly captured moments of loss in imisebenzi ka S.S Mema, Nontsizi Mgqwetho, noPascale Petit, novangile gantsho. Imisebenzi yabo ikuzobela umfanekiso ngqondweni ophilayo. Bonke abababhali bahambe indlela endinika umdla nendifuna ukuyihamba nam njengombhali omtsha obhala ngeelwimi ezimbini.,My thesis is a collection of poems and prose that explores the disjunction of losses for women and children across the two languages I inhabit, isiXhosa and English. For me, isiXhosa captures the innate musicality and deep emotions within a word or a sound that are not available to me in English. On the other hand, English readily produces visceral images that are more difficult for me to find in isiXhosa. My poems use the music and introspection of the lyric form, as well as the emotional outpouring that prose poetry allows. As a bilingual writer, I am influenced by the transference of musicality and gravity of loss conveyed in the translated and bilingual work of Isabella Motadinyane, the Russian Marina Tsvetaeva, Stephen Watson's Song of the Broken String, as well as the Spanish poets Antonio Machado. The structure of my thesis is inspired by the innovative mixed genre layout of Sindiswa Busuku-Mathese's Loud and Yellow Laughter, and the new formats of isiXhosa writing presented in Mthunzikazi Mbugwana's poetry. My work has also been shaped by the visceral imagery and briefly captured moments of loss in the work of South African poets vangile gantsho, S.S. Mema, and Nontsizi Mgqwetho, as well as the English poet, Pascale Petit.
iLahleko - Loss
Keywords: Creative writing (Higher education) -- South Africa; Xhosa poetry 21st century; South African poetry (English) 21st century; Short stories, South African (English) 21st century; Loss (Psychology) in literature; Poetry History and criticism; Bilingual authors; Bilingualism and literature; Bilingualism in literature